1980
DOI: 10.1084/jem.152.3.620
|View full text |Cite
|
Sign up to set email alerts
|

Nature of T lymphocyte recognition of macrophage-associated antigens. V. Contribution of individual peptide residues of human fibrinopeptide B to T lymphocyte responses.

Abstract: Guinea pig T lymphocyte responses to a decapeptide antigen (NH1-Asp5-Ans6-Glu7-Glu8-Gly9-Phe10-Phe11-Ser12-Ala13-Arg14-OH) of human fibrinopeptide B (hFPB) were examined using various synthetic peptide analogues containing single residue substitutions. Each analogue was examined for antigenicity as determined by an in vitro proliferative responses of hFPN-immune strain 2 guinae pig T cells. In addition, both strain 2 and strain 13 animals were immunized with each analogue and immunogenicity assessed by in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 21 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…A review of the literature suggests not. A number of examples exist of experimental results that have as a possible interpretation a two subsite structure of the antigenic determinant recognized by T cells (32)(33)(34)(35)(36)(37). The oldest example is the classic Ir gene experiment of Levine, Ojeda & Benacerraf from 1963 (32).…”
Section: Antigen Presentation Experimentsmentioning
confidence: 95%
“…A review of the literature suggests not. A number of examples exist of experimental results that have as a possible interpretation a two subsite structure of the antigenic determinant recognized by T cells (32)(33)(34)(35)(36)(37). The oldest example is the classic Ir gene experiment of Levine, Ojeda & Benacerraf from 1963 (32).…”
Section: Antigen Presentation Experimentsmentioning
confidence: 95%
“…This is particularly interesting as both peptides are symmetrical with respect to the Phe residues in positions 10 and 11 in Bf17-14. We previously (4) found that Phe 1°, as well as Arg TM, contributed to the clonal specificity of T cell responses to Bf17-14, whereas substitutions for Phe 11 eliminated antigenicity and immunogenicity and substitutions for Gly 7 and Glu 8 altered immunogenicity but not the specificity of the response. Thus, the major differences between these two peptides as far as T cell responses are concerned are the changes of Ala 13 and Arg TM in Bfl7-14 to Glu.…”
Section: Resultsmentioning
confidence: 99%
“…whose sequences are shown in Fig. l, were synthesized and purified as described previously (4). Purified protein derivative of tuberculin (PPD) was purchased from Connaught Medical Research Laboratory, Willowdale, Ontario, Canada.…”
Section: Bfl7-14mentioning
confidence: 99%
See 1 more Smart Citation
“…Spleens were teased and passed through stainless steel meshes in HBSS, and treated with Gey's hemolytic solution (8) for 2 min at 4 C to remove erythrocytes. Dead cells were removed by Ficoll-Metrizoate gradient (22) [12 parts of 14% (w/v) Ficoll in distilled water and five parts of 32 …”
Section: Methodsmentioning
confidence: 99%